Valproic Acid-Like Compounds Enhance and Prolong the Radiotherapy Effect on Breast Cancer by Activating and Maintaining Anti-Tumor Immune Function - Cai, Zuchao; Lim, David; Liu, Guochao; Chen, Chen; Jin, Liya; Duan, Wenhua; Ding, Chenxia; Sun, Qingjie; Peng, Junxuan; Dong, Chao; Zhang, Fengmei; Feng, Zhihui (Frontiers in Immunology, 2021)
Inadequate sustained immune activation and tumor recurrence are major limitations of radiotherapy (RT), sustained and targeted activation of the tumor microenvironment can overcome this obstacle. Here, by two models of a primary rat breast cancer and cell co-culture, we demonstrated that valproic acid (VPA) and its derivative (HPTA) are effective immune activators for RT to inhibit tumor growth by inducing myeloid-derived macrophages and polarizing them toward the M1 phenotype, thus elevate the expression of cytokines such as IL-12, IL-6, IFN-γ and TNF-α during the early stage of the combination treatment. Meanwhile, activated CD8+ T cells increased, angiogenesis of tumors is inhibited, and the vasculature becomes sparse. Furthermore, it was suggested that VPA/HPTA can enhance the effects of RT via macrophage-mediated and macrophage-CD8+T cell-mediated antitumor immunity. The combination of VPA/HPTA and RT treatment slowed the growth of tumors and prolong the anti-tumor effect by continuously maintaining the activated immune response. These are promising findings for the development of new effective, low-cost concurrent cancer therapy.